Developing a minimally invasive gene therapy for multiple sclerosis - Paul J.H. Nijhuis; Maurits Romijn; Roy Honing; Giselle van Zon; Inge Huitinga; Fred de Winter; Joost Verhaagen (Molecular Therapy: Methods & Clinical Development)
Multiple sclerosis (MS) is a neurological disease characterized by demyelinating lesions in the CNS. This study investigated whether a minimally invasive adeno-associated virus (AAV) vector (AAV.PHP.eB) can direct transgene expression in CNS cell types relevant to MS, including astrocytes, oligodendrocytes, oligodendrocyte precursor cells (OPCs), microglia, and neurons in experimental autoimmune encephalitis, a widely used MS model. In vivo bioluminescence imaging and histological analysis following AAV.PHP.eB-mediated gene delivery in healthy mice using the ubiquitous CAG promoter and five neural promoters (MBP, Sox10, hSyn1, gfa2, and gfaABC1D) revealed long-term, robust, and cell-type-specific activity across the brain and spinal cord. AAV.PHP.eB is capable of traversing the blood-brain barrier in experimental autoimmune encephalitis (EAE) and directs sustained and cell-type-specific transgene expression for the MBP, Sox10, hSyn1, and gfaABC1D promoters. The MBP and Sox10 promoters directed transgene expression in oligodendroglia around and within inflammatory demyelinating lesions, whereas the gfaABC1D promoter directs transgene expression in gray and white matter astrocytes and hSyn1 in neurons. The neural promoters were minimally active in the periphery, with the exception of gfa2. This methodological study is a first step toward the development of minimally invasive gene therapy to promote myelin repair and/or suppress inflammation in MS.